A estética da media art: as obras de Christa Sommerer e Laurent Mignonneau - RABELLO, Rafaelle Ribeiro (Universidade Federal do Pará, 2017)
The theoretical trends and creation activities intended to somehow walk sideby- side with the discoveries and tecno-scientific developments. The contemporary scientific and technological thoughts wide and transform material basis and the aesthetics's production mode potentials. Such transformations can be observed in the Media Art field, an attributive manifestation to the contemporary context, which the main artistic investigations are focused on Computational Art, Tele-presence Art, Iimmersion, Virtual Reality, Transgenic Art and Genetic Art. Therefore, this master thesis has the objective to investigate the Aesthetic Theories which emerge from the Media Art context and have foundations on the idea of interactivity and interface, such as the Christa Sommerer's and Laurent Mignonneau's aesthetic results idealized based on the scientific, technological and artistics' thoughts. Broadly, the notion of the “Art as a live system” is adopted in order to comprehend the interative process as a set of chained elements, subject to constant intervection.